Evidence from SMA Students' Performance on the Impact of Physics Education Technology (PhET) Simulations - Oscar Jayanagara; Chandra Lukita (International Transactions on Education Technology (ITEE), 2023)
The goal of this study is to ascertain whether simulations created using Physics Education Technology (PhET) may enhance SMAstudents' performance on particular physics topics. The performance of SMA high school students on a chosen physics topic, specifically electrodynamics, can be improved using (PhET) simulation. The performance of SMA students on a chosen physics topic, namely electrodynamics, was examined in this study using a quasi-experimental methodology. In this study, 72 SMA students participated in a quasi-experimental design with multiple-choice pre- and post-tests. The division of the class into two parts—one for the control group and the other for the experimental group—was done based on the sections that the students were in. Every day during their spare time, the experimental group was permitted to play the PhET simulation for an hour, whereas the control group received no exposure to any supplemental activities that would have caused the experiment to be successful. ideas in electrodynamics are formalized through production. Despite the students' apparent interest in the simulation, the results revealed that there was no statistically significant difference between the control and experimental groups' mean scores. Perhaps the simulations that they had experienced throughout the lectures piqued students' interests further. The study also revealed that there was not necessarily a significant difference between students' performance before and after exposure to the PhET simulation, but rather a slight improvement.